Impact of COVID-19 on mobility and participation of older adults living in Hamilton, Ontario, Canada: a multimethod cohort design protocol - Luciana G Macedo; Marla K Beauchamp; Heather Keller; Nazmul Sohel; Renata Kirkwood; Brenda Vrkljan; Elisabeth Vesnaver; Janie Astephen-Wilson; Tara Noble; Nicholas Dietrich; Paula Gardner; K Bruce Newbold; et al. (BMJ Open)
Introduction The novel COVID-19 required many countries to impose public health measures that likely impacted the participation and mobility of community-dwelling older adults. This protocol details a multimethod cohort design undertaken to describe short-term and medium-term changes to the mobility and participation of older Canadians living in the community rather than retirement facilities during the COVID-19 pandemic.Methods and analysis A longitudinal telephone (or online)-administered survey is being conducted with a random sample of older adults living within 20 km of McMaster University, Hamilton, Ontario, Canada, identified from census dissemination areas. Baseline data collection of community-dwelling older adults aged 65 years and over began in May 2020 with follow-ups at 3, 6, 9 and 12 months. The Late-Life Function and Disability Instrument and global rating of change anchors are the primary outcomes of interest. A subsample of respondents will participate in open-ended, semistructured interviews conducted over the telephone or through video-conference, to explore participants’ lived experiences with respect to their mobility and participation during the pandemic. Descriptive statistics and quantitative approaches will be used to determine changes in mobility and social and personal participation, and associated personal and environmental factors. For the interviews, qualitative data will be analysed using descriptive phenomenology.Ethics and dissemination Approval was obtained from the Hamilton Integrated Research Ethics Board of McMaster University (2020-10814-GRA). This study may inform the design of programmes that can support community-dwelling older adults during and after the COVID-19 pandemic. Findings will be disseminated through peer-reviewed publications and conferences focused on ageing.